PENGARUH HARGA, PRODUKSI, LUAS LAHAN, UMUR TANAMAN DAN PENGALAMAN BERTANI TERHADAP PENDAPATAN PETANI KELAPA SAWIT DI DESA SUKAMAJU KECAMATAN RIMBO ULU KABUPATEN TEBO - Intan Aulia Tami; Zulgani; Hardiani (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze farmer characteristics, income levels, and the influence of price, production, land area, plant age, and farming experience on the income of oil palm farmers in Sukamaju Village. The method used was descriptive quantitative with a Cobb-Douglas production function approach. Data were obtained from 58 farmers through saturated sampling and analyzed using multiple linear regression. The results showed that all variables significantly influenced income. Production was the most dominant factor, followed by farming experience and price, which had a positive effect. Meanwhile, land area and plant age had a negative effect. The return to scale value of 0.979 indicates a condition of decreasing returns to scale, so that increased inputs do not produce proportional output. Therefore, increased efficiency in the use of production factors is needed.